DAMPAK PEMANFAATAN TEKNOLOGI INFORMASI DALAM BIDANG E-COMMERCE TERHADAP PENDAPATAN USAHA MIKRO DI KABUPATEN SUMBAWA - Tryamanda, Nazula Charisna; Sudiyarti, Nining (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to determine the impact of the use of information technology in the field of e-commerce on the income of micro-businesses in Sumbawa District. The type of this study was comparative research which aims to examine the differences in income levels of micro-business actors in Sumbawa District before (X1) and after (X2) the use of information technology in the field of e-commerce. The type of data used in this study is quantitative data obtained from secondary sources through documents or financial report archives found at Butik Yana Sumbawa Besar. The data analysis technique used were two-average difference test consisting of table paired samples statistics, paired samples correlation and paired samples t-test. The results of this study showed that there was a positive and significant difference in the income levels of SMEs in Sumbawa District before and after the implementation of information technology in the field of e-commerce. These results indicate that the use of information technology in the field of e-commerce had a significant impact on the income levels of SMEs in Sumbawa District. It has been proven that the income level of micro business actors in Sumbawa District is higher after utilizing information technology in the field of e-commerce compared to the income level before utilizing information technology in the field of e-commerce.